COVID-19 and PIMS-Two Different Entities, but the Same Trigger - Lorena Elena Meliț; Cristina Oana Mărginean; Tudor Fleșeriu; Anca Meda Văsieșiu; Dana Valentina Ghiga; Ana-Maria Roxana Koller (MDPI AG, 2022)
COVID-19 and PIMS represent two novel pathologies that have challenged the medical world during the last two years on account of their being very similar, but yet very different. Our aim was to comparatively assess children with SARS-CoV-2 infection and PIMS in terms of symptoms, clinical findings, laboratory parameters, echocardiography, and evolution. Our retrospective study included 46 children with COVID-19 (group 1), and 20 children with confirmed PIMS (group 2). We found no significant differences in terms of age, gender, and originating area between the two groups. We noticed that fever was significantly more common in the PIMS group as compared to COVID-19 group (p = 0.0217). In terms of laboratory parameters, increased bilirubin and creatinine were significantly more frequent in children with COVID-19 (p = 0.0064/p = 0.0064), while hypoalbuminemia and elevated ESR were significantly more common in those with PIMS (p < 0.0001/p = 0.0127). Moreover, prognosis parameters such as D-dimers, NT-proBNP, and CK-MB were also found to be significantly higher in the PIMS group as compared to COVID-19 group (p = 0.0003/p = 0.0182/p = 0.0007). In terms of complications, most were identified in PIMS group, among which cardiac and liver impairment along with dehydration were significantly more common in children diagnosed with PIMS as compared to those detected with COVID-19. Similarly, children with PIMS had a significantly higher chance to have pathological echocardiography changes. Although difficult, the distinction between COVID-19 and PIMS is crucial for the patient's long-term outcome.